Radiation Effects in Polymeric Materials - Kumar, Vijay; Chaudhary, Babulal; Sharma, Vishal; Verma, Kartikey; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an introduction of how radiation is processed in polymeric materials, how materials properties are affected and how the resulting materials are analyzed. It covers synthesis, characterization, or modification of important materials, e.g. polycarbonates, polyamides and polysaccharides, using radiation. For example, a complete chapter is dedicated to the characterization of biodegradable polymers irradiated with low and heavy ions. This book will be beneficial to all polymer scientists in the development of new macromolecules and to all engineers using these materials in applications. It summarizes the fundamental knowledge and latest innovations in research fields from medicine to space.
Effects of Radiation on the Environment -- Radiation Physics and Chemistry of Polymeric Materials -- High-Fluence Ion Implantation of Polymers: Evolution of Structure and Composition -- Ion Beam Modification of Poly(methyl methacrylate) (PMMA) -- Radiation Induced Effects on the Properties of Polymer-Metal Nanocomposites -- Swift Heavy Ion Irradiation Effects on the Properties of Conducting Polymer Nanostructures -- Impact of Etchant Variables on the Track Parameters in CR-39 Polymer Nuclear Track Detector: A Review -- Synthesis of Hydrogels by Modification of Natural Polysaccharides Through Radiation Cross-linking Polymerization for Use in Drug Delivery -- Effects of Radiations on the Properties of Polycarbonate -- Plasma Irradiation of Polymers: Surface to Biological Mitigation -- Effects of Neutron Irradiation on Polymer -- Radiation Cross-linking for the Cable, Rubber and Healthcare Products Industry -- Energy Lossof Swift Heavy Ions: Fundamentals and Theoretical formulations.
Keywords: Polymers; Surfaces (Technology).; Thin films; Radiation dosimetry; Physical chemistry; Polymers; Surfaces, Interfaces and Thin Film; Radiation Dosimetry and Protection; Physical Chemistry